Quantification of Black bodies: Anti-black racism in research - Oyelana, Olabisi; Asirifi, Mary; Gateri, Hellen; Edwards, Fiona; Intungane, Doriane; Kimei, Janet; Khalema, Emily (My University, 2025)
It is time to start interrogating the legacy of colonialism that privileges a Eurocentric system of knowing within the Canadian education system and examine the research experiences of Black researchers. Many Black researchers continue to struggle with limited funding to conduct their research projects and many are faced with the issue of access to research mentorship. While Black scholars are restricted by these challenges, the Black populations are often researched by researchers who have little or no knowledge about their experiences. Moreover, the colonial constructs that pervade academia have relegated Black scholars and racialized groups as illegitimate knowledge producers. Our stories of lived experiences cannot be adequately represented by numbers nor by an outsider. This article argues that it is time to center the research experiences of Black researchers through the lenses of Critical race theory (CRT) and an anti-Black racism (ABR) framework. Our way of knowing creates a space for us to share and document voices alongside participants. hooks (1994) offered a way to think about personal experience as, “a way of knowing that is often expressed through the body, what it knows, what has been deeply inscribed on it through experience” (p. 36). This complexity of experience can rarely be named from a distance, neither can it be quantified into statistical data. Therefore, this article is inspired by the research agenda of Black female academics from a Canadian university. We view ourselves as legitimate knowledge producers with a keen interest in decolonizing research.
Keywords: Critical Race Theory; anti-Black racism; decolonizing research; Black bodies; legitimate knower